PATTERNS OF INTERGENERATIONAL SOCIAL MOBILITY IN LITHUANIA - Vencius, Tautvydas (Socialinė teorija, empirija, politika ir praktika, 2018)
Both scholarly analyses and main political documents have not focused enough on research into social mobility in Lithuania. Such a case is partly understandable, as the issue of ensuring social mobility has never been a prevailing one on the political agenda. Nevertheless, this issue should be substantial to politicians and the academic community, because we belong to a group of countries that are committed to implementing the idea of equal possibilities for all citizens. It is worth mentioning that unlike the objectives to reduce inequality, poverty and exclusion, seeking social mobility is beneficial in terms of different political perspectives. Thus, research into social mobility has great potential for political effect and is important for all welfare states. This research is one of the first attempts in Lithuanian to review the complexity of the notion of social mobility and the issue it raises. After distinguishing the difference between intragenerational and intergenerational social mobility, the latter will be analyzed. In accordance with factors responsible for intergenerational social mobility, theoretical insights and research conducted in this area as well as the possible manifestations of intergenerational social mobility will be examined while identifying the most influential factors and how the interaction of those factors vary among different generations. In this case, manifestations of social mobility are interpreted as the process of moving up or down the occupational scale or remaining in a stable position. Initial statistical analysis for examining general tendencies of social mobility, linear regression analysis and linear regression analysis with interaction variables have been used in this research. The aforementioned methods have shown that economic and social factors responsible for intergenerational social mobility, which have been discussed in the theoretical part, are of little significance in Lithuanian society, although the influence of education (institutional factors) is evident among different generations.